Co-gradient Li-rich cathode relieving the capacity decay in Lithium-ion batteries. (September 2022) - Wang, Hong; Liu, Fang; Yu, Ruohan; Xiao, Zhitong; Zhu, Zhu; Zhou, Liang; Wu, Jinsong
Abstract: Lithium-rich layered oxides (LLOs) are one of the promising cathode materials for next generation energy storage devices, but structural degradation and severe capacity decay during cycling have hindered applications. Here, we find cobalt effectively mitigate structural degradation and develop a simple and novel metal organic framework (MOF) treatment and surface reconstruction method to fabricate Co gradient layer on LLOs. In situ and ex situ microstructural studies show the capacity decay is mainly originated from the formation of microstructural defects such as voids and pores, continuous oxygen release and formation of spinel and rock-salt structure initiated from the surface. The reconstruction leads to the formation of an artificial layer of Co rich and Li poor spinel (Co3 O4 ) and rock-salt (CoO) structure on surface, suppressing the diffusion of cations and O −1 /O −2 anions toward the surface during cycling. The LLO-Co cathode exhibits enhanced cycling stability with a capacity retention of 94.4% at 0.2 C after 100 cycles and a high capacity of 183 mAh g −1 at 1 C, in comparison with those of untreated LLO (80.5% and 153 mAh g −1 ). This work sheds lights on better utilize rare Co resource in the development of high capacity and cyclability cathode materials for lithium-ion batteries. Graphical Abstract: A simple and novel metal organic framework treatment and surface reconstruction method is developed to fabricate a Co gradient layer on LLOs which can effectively mitigate the structural degradation in cycling. Co gradient and the bi-phase reconstruction layer at the surface effectively prevent its structure degradation and oxygen release at high voltages. ga1 Highlights: A simple and novel metal organic framework treatment is developed. The surface reconstruction method leads to Co gradient layer on LLOs. The reconstruction relieves the capacity decay in cycling.